A comparative analysis of the practice and performance of microfinance institutions in Nigeria. Issue 11 (6th November 2017) - Babajide, Abiola Ayopo; Taiwo, Joseph Niyan; Adetiloye, Kehinde Adekunle
Abstract : Purpose: The successful story of microfinance institutions is often tied to the practice and methods of credit delivery as evidence among international world class microfinance institutions across the globe. The purpose of this paper is to examine the impact of practice and methods of credit delivery employed by "non- profit" and "for-profit" microfinance institutions on financial sustainability and outreach programmes of the microfinance institutions in Nigeria. Design/methodology/approach: The study adopts the survey research design and multi-stage stratified random sampling procedure to collect data from 372 senior management staff, managing directors and board members of microfinance institutions of both groups in Nigeria. Data collected were analyzed using descriptive statistics and multiple regressions analysis. Findings: The findings suggest that the current practice and methods of credit delivery of microfinance in both "non-profit" and "for-profit" microfinance institutions have an inverse relationship with the financial sustainability and outreach programmes of the institutions. This study provides empirical evidence for the incessant failure of microfinance institutions in Nigeria. Research limitations/implications: The study therefore recommends an immediate overhaul of the methodology and practice of microfinance institutions in the country to align with international best practice. Originality/value: In spite of the huge literature on microfinance in Nigeria, there is not enough evidence to empirically prove that the practice of microfinance has affected the performance of the industry in Nigeria. This study sets out to fill that gap in the literature. The paper examines the practice of microfinancing in Nigeria vis-à-vis the performance of the microfinance institutions, categorized into NGO and microfinance bank "for-profit" institutions using international best practices from countries where microfinance is highly successful as a benchmark for deployment of microfinance in Nigeria, in order to proffer policy direction to stakeholders on steps to take to ensure viability in the microfinance subsector in Nigeria.